Perbandingan Proses Peradilan HAM Internasional dan Nasional: Studi atas Efektivitas dan Implementasi - Theresia Devanti Larantukan; Venansiu Gabur; Mardini Tae; Fadil Mas'ud; Fadil Mas’ud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The enforcement of human rights (HAM) is a crucial component of the global legal system, ensuring justice for victims of human rights violations. International and national human rights courts differ in their strengths, weaknesses, and effectiveness. This study aims to compare the two mechanisms, using case studies of the International Criminal Court (ICC) and several national systems. The ICC has the authority to handle serious violations such as genocide, war crimes, and crimes against humanity. Its strengths lie in its independence and cross-border reach, but it is hampered by political support and limited resources. In contrast, national courts are more responsive to local conditions, but are often hampered by political interference, weak institutional capacity, and legal inconsistencies. This undermines public trust in national systems. The study concludes that collaboration between international and national courts is crucial for strengthening human rights enforcement. Strengthening coordination, legal harmonization, and enhancing the capacity of national institutions are necessary for the effective implementation of international decisions. Global political support is also a determining factor in increasing the effectiveness of human rights courts and providing justice for victims of violations.